Controle de Flexão de Joelho através de Estimulação Elétrico Funcional em malha-fechada utilizando controladores $GPC$ e $RST$ em ambiente de simulação Opensim - Andrade, Aparecida Falcão de (2023)
Motor disability affects the ability to move and perform independent motor tasks, being caused by spinal cord injuries, neuromuscular diseases, and congenital conditions. In Brazil, a significant portion of the population suffers from movement disorders, affecting areas such as mobility, accessibility, education, work, and social participation. The combination of Functional Electrical Stimulation (FES) and control techniques has shown efficacy in the motor rehabilitation of lower limbs, providing improvements in function and quality of life for people with disabilities. This approach aims to selectively activate target muscles, improve coordination of movements, and restore muscular function. In this context, this study proposes to design and evaluate, in a closed-loop system, the use of GPC controller compared to the RST controller for knee flexion movement, using models identified through computational simulations with Matlab® and Opensim® software. The theoretical framework addresses concepts of control, human movement dynamics, FES, and the use of the Opensim® simulation model. Previous studies highlight the importance of combining FES with control techniques in the rehabilitation of lower limbs, providing a basis for personalized interventions. The Leg6Do f 9Musc lower limb model from Opensim® is used to study movement dynamics and biomechanics and evaluate muscular activity. The study identifies discrete models that describe the action of knee flexion and extension muscles, using simulations with Opensim® and Matlab®. Two controllers (RST and GPC) were designed and evaluated. Despite the limitations of focusing solely on knee flexion, the GPC controller showed satisfactory results compared to RST.